Jobs, Wages and the Latin American Slowdown : LAC Semiannual Report, October 2015 - de la Torre, Augusto; Ize, Alain; Beylis, Guillermo; Lederman, Daniel (Washington, DC: World Bank, 2015)
Chapter 1 of the report covers the short-term prospects and provides an analysis of the external factors affecting the region's economic slowdown. The focus is on the adjustment challenges faced by those Latin American countries experiencing a major adverse terms of trade shock, which comes after an unprecedented (in magnitude and duration) period of terms of trade bonanza. Chapter 2 discusses the key topic of this semiannual report, that is, the implications of the slowdown for labor markets – on jobs and wages. We describe the broad labor market trends observed during the boom and contrast them with the patterns observed during the slowdown. We also describe the implications of the slowdown for inequality. A corollary of the observed labor market patterns during the slowdown is that some of the gains towards greater income equality achieved in the past decade or so may be reversed, at least in part, and that we may see a divergence between labor income inequality and household income inequality, whereby the latter may rise more than the former.